Tendinopathy more frequent in high performance athletes - Leon Valladares, D.; Barrio Mateu, L. A.; Perez Leon, A.; Benitez Leon, J.; Ponce Farfan, O.; Lagos Olivos, C. (Medicina dello Sport, 2017)
BACKGROUND: It is common for high-performance athletes and by the actions they take in their motor executions (overuse, poor technique, poor heating, etc.) to present painful manifestations, which sometimes lack a definitive diagnosis. METHODS: A prospective, longitudinal study was conducted during the period of one year in high-performance athletes who came by reference to the Imaging Laboratory of the Institute of Sports Medicine. An ultrasound comparative analysis was performed for these athletes in order to perform diagnosis of tendinopathy (tendons most affected in different sports groups). In it, it was taken into account the presence or absence of synovial sheath, sports most affected and the tendons that suffered major damage. RESULTS: In the group of tendons without a synovial sheath, the most affected tendon turned to be the patellar, while in the group of tendons with synovial sheath, the highest incidence of injury was found in the long head of the biceps. The most frequent tendinopathy regarding group sports behaved: ball games (patellar), combat (long head of biceps), resistance (patellar), competitive art (long head of biceps) and fast strength and speed (patellar). CONCLUSIONS: Ultrasound permits timely and accurate diagnosis of injuries to tendons with synovial sheath without synovial sheath, facilitating the visualization of the tendon integrity